The Development of Polylactic Acid (PLA) C-Channel Connector - HAIRUL ANUAR, MUHAMMAD HARIZ ISKANDAR; ZAKARIA, NURHUSNA ILYANA; ATAN, NURUL ATIQA NAJWA; SUPAR, KHAIRI (Multidisciplinary Applied Research and Innovation, 2026)
In this project, an innovative modular connector created especially for C-channel truss systems in construction is presented. Conventional installation techniques like welding, screwing, and manual alignment are time-consuming, frequently need skilled labor, and present safety hazards on the job site. In order to overcome these obstacles, a connector was created with AutoCAD software and manufactured via 3D printing using PLA (polylactic acid) material, which is renowned for its excellent dimensional correctness, durability, lightweight nature, and environmental sustainability. The connector offers structural versatility and ease of installation by supporting a variety of truss angle configurations, such as 90°-45°-45°, 126°-27°-27°, and 140°-20°-20°. Vernier calipers were used for dimensional verification in a fitment test to assess the connector’s precision alignment and compatibility with typical C-channel profiles. The findings demonstrated that the connector provides a firm, secure fit without the need for sophisticated equipment or trained workers, thereby cutting down on assembly time and enhancing installation consistency overall. PLA is biodegradable, therefore using it not only makes the connector economical and recyclable, but it also encourages sustainable building approaches. This study offers enhancements in efficiency, structural performance, and environmental effect while illustrating a workable, secure, and scalable solution for contemporary construction needs. Additionally, it creates new avenues for future study into alternative thermoplastic materials, 3D printing integration into structural engineering applications, and modular joint design optimization.